Giardiasis in Birds - Ferrari, Elis Domingos [UNESP]; Oliveira, Bruno César Miranda [UNESP]; Da Cruz Panegossi, Mariele Fernanda [UNESP]; Dos Santos Reginaldo, Gisele Moraes [UNESP]; Nagata, Walter Bertequini [UNESP]; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2020)
The protozoan Giardia spp. is a flagellate intestinal parasite and six species are recognized, being G. agilis that affects amphibians, G. psittaci and G. ardeae that infect birds, G. microti and G. muris that can be present in rodents and G. duodenalis that can cause disease in humans and some domestic animals, according to their assemblages, ranging from A to H. The individual can be infected by consuming water and foods with the presence of cysts. The frequently clinical signs seen in the Giardia infection are delayed growth, dehydration, weight loss, and recurrent diarrhea. The occurrence of Giardia spp. in birds from a particular site demonstrates the extent of the disease, its specificity to its hosts, its risk and transmission potential.
Keywords: Birds; Giardia; Pet birds